A percepção da grande cidade na obra de Georg Heym e Mário de Andrade - Jaeckel, Volker (Contingentia, 2009)
The object of this paper is to attempt a comparison between the perception of the big city by an author of German expressionism, Georg Heym, and the Brazilian modernist Mario de Andrade. The aim is to compare the poetic visions of two cities, Berlin and São Paulo, at the beginning of the twentieth century and highlight both, the coincidences and differences in the perception of urban life, based on the ideas of the German sociologist Georg Simmel on the life of man in modernity and the stimulations of nerve impulses.